Nigeria : Publication of Financial Sector Assessment Program Documentation -- Technical Note on Strengthening Monetary and Liquidity Management. (IMF Staff Country Reports; Country Report ;, 2013)
This Technical Note focuses on strengthening of monetary and liquidity management in Nigeria. The Central Bank of Nigeria (CBN) has robust institutional framework in place to design and implement monetary policy. The CBN has also sufficient instruments for short-term liquidity management. The Monetary Policy Rate (MPR) corridor serves as a signaling device for the monetary policy stance. Although use of the overnight facilities is at the banks' discretion, the CBN is able to use repo operations and outright transactions to manage day-to-day liquidity and guide short-term interest rates toward the MPR.